Personalization and Privacy: Factors Influencing Users' Willingness to Accept Personalized Information in Multivitamin Purchases. A Case Study on Shopee. - Marhadi, Audria Ineswari Mulya; Putrawangsa, Dian; Kristiawan, Hedie; Ajie, Whisnu Trie Seno; Yap, Hedie Vincentius Mikhael; Retsuya, Christian Vega (STMIK Widya Cipta Dharma, 2025)
The e-commerce industry in Indonesia, particularly in the health sector such as multivitamin, has experienced significant growth in recent years. E-commerce platforms like Shopee leverage consumer data to offer personalized product recommendations, including in the multivitamin category. While this personalization strategy can enhance the shopping experience, concerns regarding consumer privacy, especially for health-related products, pose a major challenge. This study aims to identify the factors influencing consumers' willingness to accept personalized communication on e-commerce platforms, focusing on five key variables: perceived benefits, perceived risks, trust, privacy policy transparency, and data usage context. The study employs multiple linear regression to analyze the simultaneous and partial effects of these variables on consumers' decisions to share personal data. The results indicate that the data usage context variable has a significant partial effect, while the other variables do not show significant individual effects. However, all five independent variables collectively have a significant impact on consumers' willingness to accept personalized communication. These findings provide valuable insights for e-commerce practitioners in designing effective personalization strategies, while ensuring consumer privacy is safeguarded. Furthermore, the study contributes to privacy protection policies, particularly in the e-commerce context, by emphasizing the importance of transparency and trust in maintaining a healthy relationship between platforms and consumers.